THE INFLUENCE OF ORGANIZED ACTIVENESS AND CAMPUS FACILITIES ON LEARNING ACHIEVEMENT WITH LEARNING MOTIVATION AS AN INTERVENING VARIABLE - Chintya Ones Charli; Yosi Puspita Sari (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
Background : This study aims to examine how much influence organizational activity and campus facilities have on learning achievement with learning motivation as an intervening variable (student organizations at private universities in Padang city).. Method : The data collection technique with this survey uses a self-administered survey in which each questionnaire is distributed online using the Google Form. Result : A total of 172 people filled out the questionnaire that was distributed. All statements in the questionnaire were answered by respondents consisting of 6 (six) statements on Organizational Activeness, 10 (ten) questions, 14 (fourteen) statements for learning motivation variables and 15 (fifteen) questions for Learning Achievement. Conclusions : Based on the results of testing the direct effect hypothesis, it can be concluded that organizational activity has a significant effect on learning motivation, campus facilities have no significant effect on learning motivation, organizational activity has a significant effect on learning achievement, campus facilities have no significant effect on learning achievement, learning motivation has a significant on learning achievement, learning motivation cannot mediate organizational activity on learning achievement and learning motivation cannot mediate campus facilities on learning achievement.